Modelling the Hydrological Effects of a Levee Failure on the Lower Tisza River - Kiss, Tímea (Journal of Environmental Geography, 2015)
Along the Lower Tisza River (Hungary) the water level of the floods reached new record stages in 1998 and 2006, resulting in 80 cm increase in the peak flood level since the “great flood of 1970”. Due to the gradual weakening of the levee-system caused by the several long-lasting floods, the question has arisen, that as in case of a levee breach or failure how would it modify the hydrological parameters of the river. The aim of the research is to create a hydrological model to analyse the effects (as stage reduction, slope and stream power) of two different levee breaches: one happening before the peak of the flood and another at the time of the flood level. The simulated levee breaching happened on the Tisza River at Mindszent, and the data-set of the 2006 flood was used for the model-ling (at that time no levee failure happened in Hungary, and it was the greatest flood in history). In the simulation the levee was broken at a point, where the channel is very close and intensively eroding, thus there is a real risk of a levee failure. If the levee would be broken a well defined area (reservoir) would be flooded, surrounded by the secondary levees and the rim of the high floodplain. During the simulation the HEC-RAS 4.1. ArcGIS 10.1 and HEC-GeoRAS software were applied. The greatest changes in the hydrology of Tisza occurred in the cross section where the levee breached, though the effects propagated upstream and downstream too. Due to the water outflow from the Tisza the greatest stage reduction effect was 1.54±0.1 m. The slope conditions changed too, as it increased from 4 cm/km to 6.5 cm/km in the upstream reach, while downstream of the failure point it decreased from 3.5 cm/km to 1.9 cm/km. At the same time the stream power increased from 4 W/m to 5.5 W/m in the up-stream section, while it decreased from 3.5 W/m to 1.5 W/m in the downstream reach. Comparing the results of the simulations at different stages (one at the highest stage and one at 1.0 m lower stage) it seems that the hydrological parameters did not change considerably (1%), though in a case of a levee failure at higher the reservoir reached the maximal water level sooner, though less water was stored in it, as the fall of the river was continuous.